Over at the College - F. Todd Goodson (Educational Considerations, 2022)
Today, rural America is complex and layered, and it deserves the attention of those who have spent far too many years flying over it only to occasionally see through the clouds and wonder what those big circles are below dotting the landscape. The manuscripts in this issue chart several ways a spirit of new dialogue with rural America can begin. Authors discuss the embedded qualities of higher education demonstrates well how it is possible to anchor the work of post-secondary education in contemporary rural locations, and other perspectives on that which is possible if we engage productively with rural communities and people. This engagement is long overdue. I don’t believe it is an exaggeration to say the future of our nation depends on healing the divide that has festered entirely too long. Educators have always led the way into the most important work in our society. It is time to boldly approach this work
Keywords: rural; college